EVALUATING THE INTEGRATION OF WORD PROBLEMS, WORLD EXPERIENCE, AND MATHEMATICAL KNOWLEDGE IN YOUNG CHILDREN: Received: 10th October 2022; Revised: 2nd January 2023, 11th February 2023; Accepted: 07th March 2023 - Kwan Yuet Ling, Linda (PUPIL: International Journal of Teaching, Education and Learning, 2023)
This study arose from research conducted in a school where students aged seven to nine struggled to solve mathematical problems. The study’s goal was to find out how children make sense of their problems. Students were given a few simple arithmetic problems and then individually interviewed to determine and comprehend the difficulties that the students were experiencing. The problems’ stories involved a quantity being increased by or combined with another quantity to form a total. The quantities were small natural numbers that did not exceed 20. The findings revealed a number of problems with mathematics learning. The results were derived from how students understood the word problems, the relationship between the word problems and real-life experience, the relationship between real-life experience and mathematical knowledge, and the integration of word problems, world experience, and mathematical knowledge. How students work and verify their answers in order to better understand their thinking was observed. The usefulness of word problems in school can be realized only if students’ understanding of a particular situation can be elicited, enriched, or embellished with their experience before that experience can be re-examined in light of the theory that is applied to the real-life situation.